Виявлення малорозмірних цілей, що низько летять, методом фонової радіолокації - Матвієнко, Є. П. (ХНУРЕ, 2024)
The background radar method is pivotal in detecting small, low-flying targets. Still, conventional radar systems face challenges in effectively identifying these targets due to weak echoes and interference complexities, focusing on spectral scaling processing to refine radar signals and enhance sensitivity to small targets while minimizing interference. By fine-tuning signal frequency content, this approach offers a streamlined solution to bolster radar performance without compromising existing functionalities. Integrating spectral scaling within radar systems enhances target detection capabilities. Through refining spectral information and improving signal-to-interference ratios radar systems detect small, low-flying targets with unprecedented accuracy and reliability
Keywords: виявлення малорозмірних цілей; метод фонової радіолокації